Beyond biomass: Soil feedbacks are transient over plant life stages and alter fitness. (11th October 2017) - Dudenhöffer, Jan‐Hendrik; Ebeling, Anne; Klein, Alexandra‐Maria; Wagg, Cameron
Abstract: Plants influence associated soil biotic communities that in turn can alter the performance of the subsequently growing plants. Although such "plant–soil feedbacks" (PSFs) are considered as important drivers of plant community assembly, past PSF studies have mainly addressed plant biomass production. However, plant performance is not only the production of biomass but comprises a sequence of different life stages: from seed germination over vegetative growth up to the production of a viable progeny. Here, we assessed the effects of soil biotic communities that were previously conditioned for 3 years by a focal plant species monoculture or species mixtures on key plant life stages from germination and vegetative growth to flowering and the production of viable seeds. We used three common grassland herb species that were grown in a sterile substrate and inoculated with a sterile control soil or with living soils. Living soils were conditioned either by the focal species in monoculture or a four‐ or eight‐species mixture that included the focal species to represent a decrease in the target plants' conspecific influence on the soil communities. We show that the effect of soil biota changed from positive at the plants' juvenile life stages to neutral or negative at the plants' adult life stages and ultimately decreased plant fitness. A higher conspecific influence on the soil communities pronounced the positive effects at the juvenile life stage but also the negative effects at adult life stages. Further, we observed direct soil biotic effects on flower production and plant fitness that were not mediated by adult biomass production. This suggests that soil biotic effects may alter plant resource allocation and even may have transgenerational effects on plant fitness. Synthesis . We conclude that there is no overarching effect of soil biota that remains consistent at all the life stages of a plant. Thus, our results highlight the importance to consider plant life stage and ultimately plant fitness especially when plant–soil interactions are used to explain plant community dynamics. Abstract : Following soil biotic effects and feedbacks along the life cycles of three plant species, our study suggests that plant responses to soil biota are transient across plant life stages. Effects observed during the vegetative life stage not necessarily reflect successful plant reproduction. The temporal variability of soil biotic effects highlights the importance to consider plant responses beyond biomass production, especially when plant–soil biotic interactions are used to explain plant species coexistence and community dynamics.